2011
DOI: 10.1155/2011/724635
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Susceptibility ofMycobacterium massilienseRecovered from Wound Samples of Patients Submitted to Arthroscopic and Laparoscopic Surgeries

Abstract: Testing of rapidly growing species of mycobacteria (RGM) against antibacterial agents has been shown to have some clinical utility. This work establishes the MICs of seven antimicrobial agents following the guidelines set forth by the Clinical and Laboratory Standards Institute (CLSI) against eighteen isolates of Mycobacterium massiliense recovered from wound samples of patients submitted to minimally invasive surgery such as arthroscopy and laparoscopy. The isolates showed susceptibility to amikacin (MIC90 = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…bolletii , which was characterized by a specific rpoB sequevar (accession number EU117207) and two closely related pulsed field gel electrophoresis (PFGE) patterns, was responsible for these infections [4]. This strain was susceptible to amikacin and clarithromycin and resistant to tobramycin, ciprofloxacin, sulfamethoxazole, minocycline and doxycycline [6], [7], [8]. The strain was highly resistant to glutaraldehyde and susceptible to orthophthaldehyde and peracetic acid-based solutions [3], [9].…”
Section: Introductionmentioning
confidence: 99%
“…bolletii , which was characterized by a specific rpoB sequevar (accession number EU117207) and two closely related pulsed field gel electrophoresis (PFGE) patterns, was responsible for these infections [4]. This strain was susceptible to amikacin and clarithromycin and resistant to tobramycin, ciprofloxacin, sulfamethoxazole, minocycline and doxycycline [6], [7], [8]. The strain was highly resistant to glutaraldehyde and susceptible to orthophthaldehyde and peracetic acid-based solutions [3], [9].…”
Section: Introductionmentioning
confidence: 99%
“…abscessus subsp. massiliense isolates GO 01, GO 06, GO 07, GO 08, GO 13, and GO 18, were randomly chosen from a collection bank of isolates from a Brazilian epidemic outbreak that occurred in Goiânia, State of Goiás during 2005 and 2007 [ 5 ], and CRM0020 ( M . abscessus subsp.…”
Section: Methodsmentioning
confidence: 99%
“…massiliense infections is to use a combination of drugs to avoid the development of resistance. Currently, the most commonly used chemotherapy includes the use of clarithromycin (CLR) together with amikacin (AMK) [ 5 ], moxifloxacin (MXF) or cefoxitin (FOX) [ 6 ]. The major problem of chemotherapy, in addition to intrinsic resistance, is the development of resistant strains that vary from 4.5% resistance to CLR to 18% to FOX [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…bolletii strains. In addition, previous publications have confirmed that outbreak strains, whether harboring the pMAB01 plasmid or not, are fully susceptible to amikacin (AMI) (MIC ϭ 4 g/ml or 8 g/ml) (8)(9)(10).…”
mentioning
confidence: 93%